O cinema como contra-verbund : Harun Farocki e o trabalho com as imagens do mundo - Luís Felipe Duarte Flores (2021)
This thesis analyzes the strategies used by Harun Farocki in his critical work with the world and its images. Following a trope of the filmmaker, we draw on Alfred Sohn-Rethel's concept of Verbund [composite system] to designate the systems of ordering social life. We examine works produced between 1966 and 2014, whether cinematic, televisual, or installation-based, establishing aesthetic and political connections between them. We highlight the peculiar way in which Farocki adds critical depth to the subjects he investigates, favoring a contestatory understanding of the present. The films are grouped into four sets, according to their historical contexts and the expressive methods used. The first set includes works developed when the filmmaker, as a student at the DFFB (German Film and Television Academy in Berlin), participated in left-wing activism in the streets of West Berlin. The second set includes films and television programs made in the 1970s, during which Farocki intensified his involvement with German public television, particularly with WDR. These works deconstruct the language and conventions of the medium. The third set consists of documentaries made from the 1980s onwards, adopting an observational approach similar to direct cinema. These films subtly suspend negativity and bring forth nuanced forms of critique that complement Farocki's other areas of work. The fourth set comprises films that engage with the essayistic tradition by appropriating images of the world and weaving argumentative networks. Broadly speaking, the combinations established between various objects and technical systems in these films foster a critical view of the social fabric, enhancing our understanding of reality. Farocki's overall cinematic approach reflects two intersecting conceptions: the critique of instrumental reason, inspired by Adorno and Horkheimer's Dialectic of Enlightenment, and the critique defined by Foucault as the "art of voluntary inservitude." In both cases, cinematic resources, particularly montage, are used to critically analyze the images of the world and provide subversive keys for their epistemic deciphering.